1991
DOI: 10.1111/j.1600-0447.1991.tb03201.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of carbon dioxide‐induced panic after clonazepam treatment

Abstract: Ten patients meeting the DSM-III-R criteria for panic disorder were treated with clonazepam. Prior to clonazepam treatment and after a 5-week treatment period, patients underwent a 35% carbon dioxide challenge procedure. Following clonazepam treatment, a significant reduction in carbon dioxide vulnerability was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 5 publications
3
14
0
Order By: Relevance
“…This finding is consistent with the observation that acute 3 and long term 9 alprazolam treatment and 5-week treatment with clonazepam 10,11 are effective in reducing CO2 induced panic attacks. Perhaps the most essential part in every CO2 study is the criteria used to define laboratory panic attacks and the CO2 concentrations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with the observation that acute 3 and long term 9 alprazolam treatment and 5-week treatment with clonazepam 10,11 are effective in reducing CO2 induced panic attacks. Perhaps the most essential part in every CO2 study is the criteria used to define laboratory panic attacks and the CO2 concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…A significant reduction in 35% CO2 vulnerability was observed in ten panic disorder patients after a 5-week treatment with clonazepam 10 -mean dose 2.1 mg/day. There is also a case report 11 of a 30-year-old woman with panic disorder and phobic avoidance who responded partially to treatment with alprazolam but recovered fully while receiving clonazepam. After 5 weeks of alprazolam she had still spontaneous panic attacks but not after a 8-weeks treatment with clonazepam.…”
Section: Alprazolammentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding is consistent with the observation that acute alprazolam 19 , 10 days treatment with clonazepam 21 , long term alprazolam 20 treatment and 5-week treatment with clonazepam 18,25 are effective in reducing CO 2 induced panic attacks. Perhaps the most essential point in every CO 2 study is the criteria used to define laboratorial panic attacks and the CO 2 concentrations.…”
Section: Discussionsupporting
confidence: 82%
“…We also expect that the CO 2 challenge-test could be a useful addition tool for measuring the pharmacological response during the initial phase (6 weeks) in the treatment of PD patients. It is expected that clonazepam should block CO 2 induced anxiety attacks and other studies have reported similar results with chronic administration of clonazepam 18 and acute 19 and long term administration of alprazolam. 20 In a preliminary report 21 clonazepam was effective in blocking CO 2 panic attacks after 10 days of treatment.…”
supporting
confidence: 63%